EP.FRI.1020 The necessity of colonoscopy to rule out colorectal malignancy after computerised tomography proven diagnosis of acute diverticulitis. (28th October 2021) - Barman, S; Meney, L; Boyle, C; Collison, C; Shalli, K
Abstract: Introduction: The current Royal College of Surgeons commissioning guideline on colonic diverticular disease suggests that patients should undergo endoscopic evaluation of the colonic lumen after an episode of computed tomography (CT) proven acute diverticulitis to rule out malignancy. The necessity of routine endoscopic assessment of CT proven diverticulitis remains debatable. Aim: To establish whether routine endoscopic assessment should be carried out for patients after an episode of acute diverticulitis. Method: Data was collected retrospectively from all patients diagnosed with acute diverticulitis on CT and who subsequently had follow up endoscopic assessment from January to July 2019. Results: Total number of patients were 64.Median age of the cohort was 58.Of all patients, 48 had diagnosis of uncomplicated diverticulitis whereas 16 patients had diagnosis of complicated diverticulitis on CT scan. All patients had follow up colonoscopy after an acute attack with following findings: 2 patients had no pathology, 56 patients had diagnosis of only diverticulosis, 4 patients had both diverticulosis and polyps and 2 patients had bowel cancer. All 4 cases of polyps had benign pathology and uncomplicated diverticulitis on CT scan. Two bowel cancer patients, one had complicated diverticulitis with thickening of proximal sigmoid and the other patient had abnormal sigmoid colon suggestive of malignancy on CT scan. Conclusion: Recent meta-analysis showed no difference between diverticulitis and normal population group in terms of risk of bowel cancer. Routine colonoscopy may not be appropriate in patients with acute uncomplicated diverticulitis but endoscopic assessment after an episode of complicated diverticulitis is necessary.